Randomized Mouse Movement for Behavioural Biometric Identification - Abd. Hamid, Nazirah; Safei, Suhailan; Mohd Satar, Siti Dhalila; Chuprat, Suriayati (2013)
A biometric system consists of pattern-recognition system that recognizes a person based on either physiological or behavioral characteristics. This system can be used either to identify or verify a user. In this paper, we proposed a behavioral biometric system that used random mouse movement to identify a user. We developed an application and tested it with five users. The experiment produced 14 matching or equal to 46.67% of successful matching. The experiments are done to observe the human actions under unpredictable situation because in real life, human acts are depending on their mood, stress or the surrounding environment.